If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + -3y)(4x + 3y) = 0 Multiply (4x + -3y) * (4x + 3y) (4x * (4x + 3y) + -3y * (4x + 3y)) = 0 ((4x * 4x + 3y * 4x) + -3y * (4x + 3y)) = 0 Reorder the terms: ((12xy + 16x2) + -3y * (4x + 3y)) = 0 ((12xy + 16x2) + -3y * (4x + 3y)) = 0 (12xy + 16x2 + (4x * -3y + 3y * -3y)) = 0 (12xy + 16x2 + (-12xy + -9y2)) = 0 Reorder the terms: (12xy + -12xy + 16x2 + -9y2) = 0 Combine like terms: 12xy + -12xy = 0 (0 + 16x2 + -9y2) = 0 (16x2 + -9y2) = 0 Solving 16x2 + -9y2 = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9y2' to each side of the equation. 16x2 + -9y2 + 9y2 = 0 + 9y2 Combine like terms: -9y2 + 9y2 = 0 16x2 + 0 = 0 + 9y2 16x2 = 0 + 9y2 Remove the zero: 16x2 = 9y2 Divide each side by '16'. x2 = 0.5625y2 Simplifying x2 = 0.5625y2 Take the square root of each side: x = {-0.75y, 0.75y}
| 49.95=45.50 | | 2a-7=9-8-4a+5a | | 5(2x+3)-3(4x-1)=12 | | 3(-2x-2)=x+3 | | (a-8/12)=(2a+5/3) | | -6x+3=18 | | 6/16= | | 15(x-3)=-8-7 | | 7x+4-5=7y-8 | | (4t^2-t-9)(4t^2+4t-1)= | | x^2+2.25-36=0 | | 60+10x=5(x+20) | | -3(c-6)=-3-6 | | -5x-7=2x+14 | | 3x-7-5x=3-4x | | 4(a-3)=8a-(4a+12) | | 3[3u-6]=18 | | 14x+2x=-6-3x | | (3x-4)(5x^2-2x+6)= | | 7x+4-5=2x-2 | | 8y+4=7y-8 | | -12+8x=-6(8x+2)+5x | | 7y-4+6=2y+4 | | .6w+2=26 | | ln(13)-ln(2x)=ln(52) | | 3x^2-4=4x | | 8+8q=9+7q | | m^2+6m-91= | | -5=x/2-5 | | -8c+5=-2-4c | | 38-6b=4(4b+4) | | x+.80(2)=.90(x+2) |